Menstrual hygiene practice between rural and urban high school adolescent girls in Bangladesh - Sultana, Rajea; Shom, Ela Rani; Khatun, Fahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Menstruation is a natural, normal biological process experienced by all adolescent girls and women. Urinary tract infection, reproductive tract infection and complication during pregnancy are the impact of poor menstrual hygiene practices. The aim of this study is to compare the menstrual hygiene practice between rural and urban high school adolescent girls in Bangladesh. Methods: A descriptive comparative study design was used. Cluster sampling technique was used to select 120 study participants. The data were collected through self-reported questionnaire by structured questionnaires. In descriptive statistics; frequency, percentage, mean, standard deviation and in inferential statistics; chi-square-test, t-test was used to compare the menstrual hygiene practice between rural and urban. Data was analyzed using SPSS version 23. Results: There was significant difference between rural and urban girls regarding mean age at menarche (5.50, p = 0.000). There was a statistically significant difference between rural and urban girls using of sanitary pad (30.54, p = 0.000) and reusable cloth (38.92, p = 0.000). Conclusions: This study found that menstrual hygiene practice (MHP) was more among the urban high school adolescent girls than in the rural high school adolescent girls. The result provides baseline information regarding menstrual hygiene practice (MHP) among rural participants that’s why need more emphasize on health promotion and counseling program regarding menstrual hygiene practice (MHP) among rural and primary level health sectors in Bangladesh.